Tolerance of Warmer Temperatures Does Not Confer Resilience to Heatwaves in an Alpine Herb - Notarnicola, Rocco F.; Nicotra, Adrienne B.; Kruuk, Loeske E. B.; Arnold, Pieter A. (Frontiers in Ecology and Evolution, 2021)
Climate change is generating both sustained trends in average temperatures and higher frequency and intensity of extreme events. This poses a serious threat to biodiversity, especially in vulnerable environments, like alpine systems. Phenotypic plasticity is considered to be an adaptive mechanism to cope with climate change in situ, yet studies of the plastic responses of alpine plants to high temperature stress are scarce. Future weather extremes will occur against a background of warmer temperatures, but we do not know whether acclimation to warmer average temperatures confers tolerance to extreme heatwaves. Nor do we know whether populations on an elevational gradient differ in their tolerance or plasticity in response to warming and heatwave events. We investigated the responses of a suite of functional traits of an endemic Australian alpine herb, Wahlenbergia ceracea, to combinations of predicted future (warmer) temperatures and (relative) heatwaves. We also tested whether responses differed between high- versus low-elevation populations. When grown under warmer temperatures, W. ceracea plants showed signs of acclimation by means of higher thermal tolerance (Tcrit, T50 and Tmax). They also invested more in flower production, despite showing a concurrent reduction in photosynthetic efficiency (Fv/Fm) and suppression of seed production. Heatwaves reduced both photosynthetic efficiency and longevity. However, we found no evidence that acclimation to warmer temperatures conferred tolerance of the photosynthetic machinery to heatwaves. Instead, when exposed to heatwaves following warmer growth temperatures, plants had lower photosynthetic efficiency and underwent a severe reduction in seed production. High- and low-elevation populations and families exhibited limited genetic variation in trait means and plasticity in response to temperature. We conclude that W. ceracea shows some capacity to acclimate to warming conditions but there is no evidence that tolerance of warmer temperatures confers any resilience to heatwaves.